2022
DOI: 10.5935/0103-507x.20220018-en
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mechanical power and its components on mechanical ventilation in SARS-CoV-2

Abstract: Objective To analyze the influence of mechanical power and its components on mechanical ventilation for patients infected with SARS-CoV-2; identify the values of the mechanical ventilation components and verify their correlations with each other and with the mechanical power and effects on the result of the Gattinoni-S and Giosa formulas. Methods This was an observational, longitudinal, analytical and quantitative study of respirator and mechanical power parameters in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Driving pressure is considered a predictor of mortality that may not change with prone positioning, 30 however, reductions in transpulmonary driving pressure have been demonstrated to be more reliable due to its greater precision of the exclusion of the chest wall component and present the stress applied to the lung parenchyma. 31 Prone positioning is considered a good strategy to reduce VILI, as titrating PEEP to lower values during prone positioning correlates with a reduction in transpulmonary driving pressure and mechanical power.…”
Section: Discussionmentioning
confidence: 99%
“…Driving pressure is considered a predictor of mortality that may not change with prone positioning, 30 however, reductions in transpulmonary driving pressure have been demonstrated to be more reliable due to its greater precision of the exclusion of the chest wall component and present the stress applied to the lung parenchyma. 31 Prone positioning is considered a good strategy to reduce VILI, as titrating PEEP to lower values during prone positioning correlates with a reduction in transpulmonary driving pressure and mechanical power.…”
Section: Discussionmentioning
confidence: 99%
“…According to Chi and colleagues, 20 As Franck & Franck have pointed out, 23 the correlations between components and MP have an influence on their high momentary values and correlations of components amongst each other influenced their behavior throughout the study period. In this research, we demonstrated that the mortality was related to higher values of MP, both in short and extended periods of ventilation.…”
Section: Discussionmentioning
confidence: 99%